Immunogenetic profiling to predict risk of invasive fungal diseases : where are we now? - Cunha, Cristina (2011)
Invasive fungal diseases remain nowadays life-threatening conditions affecting multiple clinical settings. The onset of these diseases is dependent on numerous factors, of which the "immunocompromised" phenotype of the patients is the more often acknowledged. However, and despite comparable immune dysfunction, not all patients are ultimately susceptible to disease, suggesting that additional risk factors, likely of genetic nature, may also be important. In the last years, genetic variants in several immune-related genes have also been proposed as major determinants of the susceptibility pattern of high-risk patients to invasive fungal diseases. Altogether, these findings highlighted the crucial significance of the individual genetic make-up in defining susceptibility to infection, providing a compelling rationale for the introduction of the immunogenetic profile as a risk prediction measure that may ultimately help to guide clinicians in the use of prophylaxis and preemptive fungal therapy in high-risk patients.